2018
DOI: 10.1155/2018/3749725
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Clastic Dykes and Soft-Sediment Deformation Structures in the Mamfe Basin, South-West Region, Cameroon: Field Geology Approach

Abstract: This paper aims to investigate the genesis of clastic dykes and soft-sediment deformation structures in the Mamfe Basin, South West-Region, Cameroon. Results from this study portray the following: (1) The clastic dykes are extrusive and were generated from preexisting soft-sediments that penetrate fissures caused by seismic activity. It can be concluded that clastic dykes originate from seismic shacking, probably induced by volcanic-tectonic activity and magmatic dykes that cut across the Precambrian and Creta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Phylogenies are a key mean in biogeographic and molecular evolutionary studies (Avise, 2009;Avise et al, 2000) and increasingly recognized as being essential to research that aim to reconcile biological and geological information to reconstruct Earth surface processes such as mountain building (Hoorn et al, 2013;Mulch & Chamberlain, 2018). In fact, organismal evolution offers an independent line of evidence for the emplacement of major topographical features, which have been proved valid in refining the timing of events substantiated by geologic record (Donoghue & Benton, 2007;Richardson et al, 2018). Specifically, several studies have demonstrated the suitability of phylogenetic data for addressing the timing and complexity of orogenic events, e.g., the Andean uplift and the formation of the Qinghai-Tibetan region (Antonelli et al, 2009;Luebert & Muller, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenies are a key mean in biogeographic and molecular evolutionary studies (Avise, 2009;Avise et al, 2000) and increasingly recognized as being essential to research that aim to reconcile biological and geological information to reconstruct Earth surface processes such as mountain building (Hoorn et al, 2013;Mulch & Chamberlain, 2018). In fact, organismal evolution offers an independent line of evidence for the emplacement of major topographical features, which have been proved valid in refining the timing of events substantiated by geologic record (Donoghue & Benton, 2007;Richardson et al, 2018). Specifically, several studies have demonstrated the suitability of phylogenetic data for addressing the timing and complexity of orogenic events, e.g., the Andean uplift and the formation of the Qinghai-Tibetan region (Antonelli et al, 2009;Luebert & Muller, 2015).…”
Section: Introductionmentioning
confidence: 99%